2015
DOI: 10.14569/ijacsa.2015.060105
|View full text |Cite
|
Sign up to set email alerts
|

Review of Cross-Platforms for Mobile Learning Application Development

Abstract: Abstract-Mobile learning management systems are very important for training purpose. But considering the present scenario, the learners are equipped with a number of mobile devices that run by different operating systems with diverse device features. Therefore, developing a mobile application for different platforms is a cumbersome task if appropriate tools and techniques are not practiced. There are three categories of mobile application namely native, web based and hybrid. For mobile learning system, hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…However, the learner were equipped with a number of mobile devices that run by different operating system with diverse device features. To develop cross-platform mobile learning system would receive increased interest [10]. In addition, the developers paid attention to how to improve users' learning efficiency by using mobile learning APP [11], by means of the method of quantitative to analyze the effect of the use of smartphones and APPs by college students, found that mobile learning could bring students more practice chances, not only establishing contact with future career, but also fostering collaborative work among students and professors.…”
Section: Mobile Learning Appmentioning
confidence: 99%
“…However, the learner were equipped with a number of mobile devices that run by different operating system with diverse device features. To develop cross-platform mobile learning system would receive increased interest [10]. In addition, the developers paid attention to how to improve users' learning efficiency by using mobile learning APP [11], by means of the method of quantitative to analyze the effect of the use of smartphones and APPs by college students, found that mobile learning could bring students more practice chances, not only establishing contact with future career, but also fostering collaborative work among students and professors.…”
Section: Mobile Learning Appmentioning
confidence: 99%
“…For hybrid apps JQuery library and PhoneGap is dominant environment. Nabil Litayem, Bhawna Dhupia, Sadia Rubab [8] have contrasted various platforms, and with the help of quizzes and assignment application example they came up with solution that hybrid application is best suitable solution for mobile application development. They suggested that instead of reimplementation of applications with same functions, first compare strength of each platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the application requirement, we determine the category adequate to our requirements [8]. Firstly, let us discuss about all of them in detail.…”
Section: Categories Of Mobile Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Driven by the Internet of things, high-speed mobile networks and cloud computing technology, the popularity and update of smart devices represented by smart phones and PAD are particularly fast [1]. These electronic products are collectively referred to as mobile application terminals, which are essential in the pursuit of innovation and the progress of the college community.…”
Section: Introductionmentioning
confidence: 99%